HAKEKAT CINTA PERSEPEKTIF ERICH FROMM SEBAGAI REFLEKSI PROSES KOMUNIKASI DALAM KEHIDUPAN SOSIAL (Vidya Darsan: Jurnal Mahasiswa Filsafat Hindu, 2024)
Understanding the nature of love makes humans increasingly aware of the importance of livingside by side and living a life with good communication between each other. Becausecommunication is one of the main pillars in every relationship and social life, because goodcommunication plays a very important role in creating healthy and harmonious relationships.This research uses a literature study method using various sources according to the field ofstudy, research journals and books as sources of literacy. The aim of this research is to discussthe nature of love from Erich Fromm as a reflection of the communication process in sociallife. The results and discussion show errors in interpreting the meaning of love in thecommunication process, resulting in misunderstandings between fellow humans in social life.So it is necessary to understand the concept of love from Erich Fromm, according to Fromm,love is an active force within humans, so when humans understand love from within themselves,it produces harmony. Sincere love according to Fromm is Standing in (establish) no Fallingfor (falling), love grows within oneself, the feeling of love and the concept of love begins withself-awareness. Falling in love is the easiest thing in this world. But staying or staying in loveis a difficult thing. In this way, understanding the concept of love is very important in thecontinuity of human social life.
Keywords: essence of love, communication, erich fromm